Two hits revisited again. - Tomlinson, I; Roylance, R; Houlston, R (2001)
INTRODUCTION AND METHODS: Since the concept of the "two hit hypothesis" was introduced over 20 years ago, a wealth of genetic data has accumulated on the mutations found at tumour suppressor loci. Perhaps surprisingly, these data conceal large gaps in our knowledge which genetic and functional studies are beginning to uncover. The "two hit hypothesis" must be updated to take account of this new information. RESULTS AND DISCUSSION: Here, we discuss both the results of recent studies and some of the questions that they highlight. In particular, how valid are conclusions from inherited Mendelian syndromes when applied to sporadic cancers? Why is allelic loss so common and how does it occur? Are the "two hits" random or interdependent? Is abolition of protein function always optimal for tumorigenesis? Can "third hits" occur and, if so, why? How can mismatch repair deficiency and the methylator phenotype be incorporated into the "two hit" hypothesis? We suggest that the "two hit hypothesis" is not fixed but is evolving as our knowledge expands.